Organizational politics and multisource feedback: An opportunity or a threat? - Greguras, G. J. (Institutional Knowledge at Singapore Management University, 2004)
Despite favorable attitudes being critical to the viability of multirater systems, little is known about the factors that impact rater attitudes. Results from a field study demonstrated that perceptions of organizational politics negatively relate to rater acceptance and cost-benefit evaluations and that these relationships were not moderated by one’s understanding, control, or rater perspective. Results indicated that supervisors held the most favorable attitudes and that experienced raters held more favorable attitudes than those without experience.